Cystic Fibrosis Diagnosis and Protocols, Volume II: Methods and Resources to Understand Cystic Fibrosis - Amaral, Margarida D.; Kunzelmann, Karl (Methods in Molecular Biology, Methods and Protocols, 2011)
Despite the many milestones in cystic fibrosis (CF) research, progress toward curing the disease has been slow, and it is increasingly difficult to grasp and use the already wide and still growing range of diverse methods currently employed to study CF so as to understand it in its multidisciplinary nature.  Cystic Fibrosis: Diagnosis and Protocols aims to provide the CF research community and related researchers with a very wide range of high-quality experimental tools, as an easy way to grasp and use classical and novel methods applied to cystic fibrosis.  Volume II: Methods and Resources to Understand Cystic Fibrosis focuses on pathophysiology, Omics approaches, and a variety of key resources recently made available for CF research.  Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Comprehensive and practical, Cystic Fibrosis: Diagnosis and Protocols will provide readers with optimal working tools to address pressing questions in the best technical way, while helping all of us, as a research and clinical community, to move faster hand-in-hand toward unravelling the secrets of this challenging disorder and cure it